Le paradoxe de l’autonomie en contexte scolaire - Raphaëlle Raab (Éducation et Socialisation)
This paper grew out of a concern. It arose in a study on the organization of favorable conditions to empowerment of Kindergarten pupils. It relates to an axiological unthought, in devices autonomous work, related to competence of autonomy that seems to highlight desirable and expected in the school context, without knowing exactly what we are talking about autonomy when and how it is constructed. In considering the autonomy conceptual field, we measure how this concept refers to visions and sometimes conflicting values. In the school context, what conceptions of autonomy the teacher will promote, transmit or reproduce? If all the purposes and the practices aren't equal, how to identify? And how to make choices of action in the service of learner empowerment? This question has commissioned review and modeling of different possible visions of the autonomy project, as well as a reflection on the paradox created by the injunction of autonomy in school context.